2021
DOI: 10.1002/adfm.202102913
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Carbon Felt Electrode with N‐Rich Defects Enables a Long‐Cycle Zinc‐Bromine Flow Battery with Ultrahigh Power Density

Abstract: Zinc-bromine flow batteries (ZBFBs) are regarded as one of the most promising technologies for energy storage owing to high energy density and low cost. However, the sluggish reaction kinetics of Br 2 /Br − couples and zinc dendrite issue lead to low power density and poor cycle stability. Herein, a multifunctional carbon felt-based electrode (NTCF) with N-rich defects is fabricated for ZBFBs. The defects with abundant N-containing groups on carbon fibers of NTCF provide high catalytic activity on Br 2 /Br − r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Water molecules were pushed out from the primary solvation shell of (Zn­(H 2 O) 6 ) 2+ , thus reducing the number of active water molecules near the anode surface and constraining corresponding adverse reactions. Second, glucose molecules tended to absorb parallel to the zinc slab (Z-GP) rather than vertical (Z-GV). ,, The adsorption of glucose thus shielded the cutting-edge electric field and increased the nucleated overpotential of zinc, leading to uniform zinc deposition. As a result, the assembled symmetric cell could run stably for more than 2000 h at 1 mA cm –2 with 1 mAh cm –2 .…”
Section: Mitigation Strategies For Challenges Related To Zinc-based B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Water molecules were pushed out from the primary solvation shell of (Zn­(H 2 O) 6 ) 2+ , thus reducing the number of active water molecules near the anode surface and constraining corresponding adverse reactions. Second, glucose molecules tended to absorb parallel to the zinc slab (Z-GP) rather than vertical (Z-GV). ,, The adsorption of glucose thus shielded the cutting-edge electric field and increased the nucleated overpotential of zinc, leading to uniform zinc deposition. As a result, the assembled symmetric cell could run stably for more than 2000 h at 1 mA cm –2 with 1 mAh cm –2 .…”
Section: Mitigation Strategies For Challenges Related To Zinc-based B...mentioning
confidence: 99%
“…Second, glucose molecules tended to absorb parallel to the zinc slab (Z-GP) rather than vertical (Z-GV). 65,93,94 The adsorption of glucose thus shielded the cutting-edge electric field and increased the nucleated overpotential of zinc, leading to uniform zinc deposition. As a result, the assembled symmetric cell could run stably for more than 2000 h at 1 mA cm −2 with 1 mAh cm −2 .…”
Section: Mitigation Strategies For Challengesmentioning
confidence: 99%
“…Thus far, many efforts have been devoted to obviating these shortcomings, using 2D h-BN. The incorporation of 2D h-BN into ZFBs is made through three major pathways: (1) modification of the electrolyte chemistry, (2) reinforcing membranes, and (3) changing the battery configuration [87,88].…”
Section: Zinc Flow Batteries (Zfbs)mentioning
confidence: 99%
“…However, it was concluded that for higher current densities, electrodes covered with oxygen functional groups on the surface were preferred. W. Lu doped carbon felt electrodes with nitrogen, reaching an EE of 63.07% at 180 mA cm −2 , with a more uniform deposition of zinc on its surface [252]. Mariyappan and coworkers studied the effect of adding a low loading of platinum on graphite felt using a pulsed laser deposition.…”
Section: Zinc-bromine Flow Batteriesmentioning
confidence: 99%